Safety of cold snare polypectomy with periprocedural antithrombotic agents for colorectal polyps: a systematic review and meta-analysis. (February 2022) - Yeh, Jen-Hao; Wang, Wen-Lun; Lin, Chih-Wen; Lee, Ching-Tai; Tseng, Cheng-Hao; Hsiao, Po-Jen; Liu, Yu-Peng; Wang, Jaw-Yuan
Background: We aimed to study the safety of cold snare polypectomy (CSP) for colorectal polyps in patients administered periprocedural antithrombotic agents. Methods: We searched the PubMed, Embase, and Cochrane Library databases through June 2021. The primary outcomes were the rates of delayed and immediate bleeding (requiring endoscopic hemostasis). Secondary outcomes included thromboembolic events. Meta-analysis using odds ratios (ORs) and corresponding 95% confidence intervals (CIs) was performed to compare the outcomes. Results: Seventeen studies, including five randomized trials, were included. Over 96% of polyps were ⩽1 cm. The pooled rates of delayed and immediate bleeding for patients receiving CSP and periprocedural antithrombotic agents were 1.6% and 10.5%, respectively. Both the delayed (OR = 4.02, 95% CI = 1.98–8.17) and immediate bleeding (OR = 5.85, 95% CI = 3.84–8.89) rates were significantly higher in patients using periprocedural antithrombotic agents than in non-users. Although both antiplatelet agents and anticoagulants increased the risk of delayed bleeding, the risks associated with the use of direct oral anticoagulants (DOACs; 2.5%) or multiple agents (3.9%) were particularly high. Compared to their counterparts, diminutive polyps and uncomplicated lesions not requiring hemoclipping were associated with lower risks of delayed bleeding (pooled estimates of 0.4% and 0.18%, respectively). Thromboembolic risk was similar among patients using and not using periprocedural antithrombotic agents. Conclusions: CSP with periprocedural antiplatelet agents and warfarin may be feasible, especially for diminutive polyps. However, drug discontinuation should be considered with the use of DOACs or multiple agents which entail higher bleeding risk even with hemoclipping.